Synthesis and Crystal Structure of Ni[phen(DTC)2H2O]+0.5H2O - Bi, Jian-Hong; Wang, Hong-Fang; Huang, Zi-Xian; Bi, Wen-Tao; Hu, Nai-Liang (Asian Journal of Chemistry, 2010)
A novel complex Ni[phen(DTC)2H2O]·0.5H2O, where phen = 1,10- phenanthroline and DTC is biphthalate, was synthesized and characterized by IR spectra, elemental analysis and single-crystal X-ray. The crystal is orthorhombic, space group Pbcm with unit cell parameters: a = 11.6669(6) Å, b = 11.1701(6) Å, c = 14.0370(6) Å, α = 90º, β = 90º, γ = 90º, V = 1829.31(16) Å3, Z = 4, Mr = 430.05, Dc = 1.561Mg/cm3, μ = 1.099 mm-1, F(000) = 884, T = 293(2) K, R = 0.0351, wR = 0.0930 with I > 2σ(I). The crystal structure analysis shows that the nickel(II) is a five-coordinated in a slightly distorted tetragonal pyramid.